Food banks, welfare, and food insecurity in Canada. Issue 9 (26th August 2014) - Tarasuk, Valerie; Dachner, Naomi; Loopstra, Rachel
Abstract : Purpose: – Similar to the recent emergence of food banks in other affluent nations, the genesis and ultimate entrenchment of food banks in Canada has been tightly intertwined with the dismantling of the welfare state. Through an examination of Canadian data, the authors elucidate the implications of entrenching voluntary, extra-governmental, charitable food assistance programs as an adjunct to publicly funded social assistance programs. The paper aims to discuss these issues. Design/methodology/approach: – Publicly available food bank reports, population health survey data, and the results of a study of low-income families in Toronto are reviewed to examine the food security status of social assistance recipients and their use of food banks. Findings: – In 2012, 70 percent of households in Canada who were reliant on social assistance were food insecure. Social assistance recipients comprise at least half of food bank clientele and have done so for as long as this information has been tracked, but the assistance provided by food banks appears insufficient to alter households' food insecurity. Although food banks currently distribute over 200 million pounds of food annually, the scale of their operations pales in comparison to the food needs of those who seek their help. Originality/value: – In the 30 years since food banks began in Canada, there has been considerable research into this response, as well as extensive population monitoring of food insecurity. Canada provides an informative case study of an affluent country's long-term dependency on charitable food assistance and the impact this has on the food insecurity of those reliant on social assistance programs.